The Prediction of Bankruptcy using Altman Z-Score Model (Case Study in BRI Bank, BNI Bank, Mandiri Bank, BTN Bank) - Mrs Herlin (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
Based on the calculation of the Altman model in predicting bankrupt at PT. Bank Rakyat Indonesia (Persero) Tbk in 2014, 2015, 2016, PT. Bank Mandiri (Persero) Tbk in 2014 and 2015 and is PT.Bank Tabungan Negara (Persero) Tbk in 2014 with a score of Z-score above 2.99 indicates that included in the company healthy or not potential to go bankrupt. Companies included in the category of unhealthy or potential companies to go bankrupt with a Z-score of less than 1.81 ie PT. Bank Tabungan Negara (Persero) Tbk in 2014 with a Z-score of 1.405 (<1.81). Companies included in the Gray Area (unpredictable) are PT. Bank Negara Indonesia (Persero) Tbk 2015 with Z-score of 2, 753 and year 2016 with Z-score 2,858. PT Bank Tabungan Negara in 2015 and 2016 with Z-score of 2,138 and 1,906 and PT. Bank Mandiri (Persero) Tbk in 2016 which shows the value of Z-score of 2,168.